Allopatric and Sympatric Drivers of Speciation in Alviniconcha Hydrothermal Vent Snails. (13th July 2020) - Breusing, Corinna; Johnson, Shannon B; Tunnicliffe, Verena; Clague, David A; Vrijenhoek, Robert C; Beinart, Roxanne A
Abstract: Despite significant advances in our understanding of speciation in the marine environment, the mechanisms underlying evolutionary diversification in deep-sea habitats remain poorly investigated. Here, we used multigene molecular clocks and population genetic inferences to examine processes that led to the emergence of the six extant lineages of Alviniconcha snails, a key taxon inhabiting deep-sea hydrothermal vents in the Indo-Pacific Ocean. We show that both allopatric divergence through historical vicariance and ecological isolation due to niche segregation contributed to speciation in this genus. The split between the two major Alviniconcha clades (separating A. boucheti and A. marisindica from A. kojimai, A. hessleri, and A. strummeri ) probably resulted from tectonic processes leading to geographic separation, whereas the splits between co-occurring species might have been influenced by ecological factors, such as the availability of specific chemosynthetic symbionts. Phylogenetic origin of the sixth species, Alviniconcha adamantis, remains uncertain, although its sister position to other extant Alviniconcha lineages indicates a possible ancestral relationship. This study lays a foundation for future genomic studies aimed at deciphering the roles of local adaptation, reproductive biology, and host–symbiont compatibility in speciation of these vent-restricted snails.